Range dynamics in sibling species: facts and reconstructions for the mammal fauna of Eastern Europe - Zagorodniuk, I. (Theriologia Ukrainica, 2019)
The specifics of distribution and status of local mammal species of sibling complexes demonstrating signs of significant either current or recent range dynamics are considered. These species complexes comprise pairs of sibling and morphologically close species, which until recently have not been unambiguously distinguished, thus it was impossible to analyse their range dynamics. However, range dynamics of this group of species is of great interest since it determines the emergence of high species diversity and realisation of mechanisms of compact organisation of communities that include close species. The amassed by today knowledge on distribution of species and the identification criteria developed for some of those species based on collection specimens allow to analyse changes in their distribution ranges. Such data in most cases allow to perform reconstructions and to develop respective hypotheses on dispersal routes of species in the region. In total, 9 species complexes were considered. Ranges of species that by direct or indirect evidence demonstrate changes in the area of their distribution and in the same time change the system of interspecific spatial relationships within each group are described. These spatial relationships can vary from allopatry to marginal or significant sympatry. Such complexes of “small” species were described in the composition of former “large” polytypic species with signs of invasions or expansions of their components among bats (Plecotus auritus + austriacus, Pipistrellus pipistrellus + pygmaeus, Eptesicus serotinus + lobatus) and rodents (Spermophilus suslicus + odessanus, Microtus arvalis + obscurus, Mus musculus + spicilegus). Similar but less expressed signs can be also traced in some other groups (Spalax zemni + arenarius, Sylvaemus sylvaticus + whiterbyi, Capreolus capreolus + pygargus). Distribution maps for all these species complexes are presented with reconstructions of possible directions of their dispersal through the territory of the region (Ukraine and adjacent countries). Zones of prochoresis, where these species most likely were absent in the recent past, are determined and analysed. The time and pace of expansion of “small” species in the region are estimated. The significance of morphological criteria of species and the possibilities of revision of old collection specimens to analyse temporal changes of biota are shown as well as the importance of cartographic data for such analysis. By using data from revisions, it is possible to estimate geographical tendencies and velocity of expansion for many species, including those that represent groups of morphologically close or sibling species.